2019
DOI: 10.1186/s13601-019-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of major mite allergens from European standardized commercial extracts for in vivo diagnosis: addressing the need for precision medicine

Abstract: Background Skin prick testing is the first-line interventional method to diagnose IgE mediated allergic diseases. Methodological differences in manufacturing processes and extract standardization may lead to variations in the reagent quality and potency. The current study evaluates sixteen commercially available Dermatophagoides pteronyssinus and Blomia tropicalis extracts for allergy diagnosis from different European manufacturers regarding al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…SPT has several contraindications, for example it cannot be used in patients with extensive eczema, dermographism, urticaria with or without angioedema (36), or in patients under medication that may interfere with the test results, such as antihistamines, glucocorticoids, and some classes of antidepressants (31). Another limitation is the fact that allergen extracts are biological mixtures, containing different concentrations of allergens, depending on the extraction method; therefore, results obtained with allergen extracts from different manufacturers can vary greatly (37,38). These variations are even more relevant when the biological extracts are used for allergen immunotherapy (39).…”
Section: Discussionmentioning
confidence: 99%
“…SPT has several contraindications, for example it cannot be used in patients with extensive eczema, dermographism, urticaria with or without angioedema (36), or in patients under medication that may interfere with the test results, such as antihistamines, glucocorticoids, and some classes of antidepressants (31). Another limitation is the fact that allergen extracts are biological mixtures, containing different concentrations of allergens, depending on the extraction method; therefore, results obtained with allergen extracts from different manufacturers can vary greatly (37,38). These variations are even more relevant when the biological extracts are used for allergen immunotherapy (39).…”
Section: Discussionmentioning
confidence: 99%
“…According to several studies based on Indian D. pteronyssinus products, [28,34] the contained proteins of the extracts were low, even zero, [28] and the mean wheal sizes were smaller than the standard extracts from America [34] . Even in a study of extracts from European products, the useful protein concentrations varied from product to product (Der p1 1.21 to 30.16 μg/mL, Der p2 0.55 to 20.49 μg/mL) [29] . Second, the diagnostic accuracy of the PUMCH allergen extracts was almost equivalent to that of other products on the market [Table 5] but had a larger sample.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, previous studies have confirmed that certain natural Dermatophagoides spp. and Blomia tropicalis extracts lack important allergens showing a considerable variability in the allergen composition and content (23)(24)(25). Moreover, it has been shown that the concentration of major allergens correlates with the biological potency and IgE reactivity of allergen extracts (26).…”
Section: Diagnosis Of Mite Armentioning
confidence: 99%